The Influence of Service Quality, Food Quality, Price, and Physical Environment on Customer Satisfaction and Customer Loyalty - Gracia Datu, Shania Syalomita; Adma Sari Sitepu (International Journal of Economics (IJEC), 2026)
Strongly embedded customer loyalty impacts consumption behavior. To win business competition, loyal customers are the main goal of the culinary industry through achieving customer satisfaction. Maintaining customer satisfaction, through: service quality as one of the main weapons to maintain prestige value by providing more satisfaction; food quality as an important component in the production process; price which has a significant influence because high or low product prices affect product sales, and the physical environment creates a first impression and influences customers' initial perceptions of service or food quality. This study aims to identify the influence of service quality, food quality, price and physical environment through customer satisfaction on customer loyalty. Sampling used a purposive sampling technique, namely customers consuming takeaway or dine-in at least twice in the past month, minimum age 18 years - maximum 47 years, domiciled in Bekasi City, processing data from 200 respondents using SEM PLS. The results showed that service quality, food quality, price and physical environment have a positive effect on customer satisfaction and customer satisfaction has a positive effect on customer loyalty. Further research can explore other relationships such as celebrity endorsers, brand love, brand awareness, brand image, brand trust and other variables